Desain Pembelajaran Diferensiasi Bermuatan Project Based Learning (PBL) Dalam Meningkatkan kompetensi 4C Dalam Pembelajaran Bahasa Arab - Nuraini, Ayat; Ade Novit Syahputra (Journal of Education and Social Culture, 2025)
This article the author tries to convey ideas related to planning design for the implementation of differentiation learning designs in Arabic lessons with competency content. 4C for students. Learning strategies that contain 4C aim to create students to have learning patterns and critical, creative and skilled mindsets that are able to develop innovative innovations. Differentiation learning strategies can be carried out in 3 forms, namely 1) content 2) process and 3) product. Content differentiation is carried out through the readiness, interests and learning profiles of students. Process differentiation is carried out with tiered activities, developing varied activities, and using groupings of students according to abilities, readiness and interests. Product differentiation can be done through giving choices on how students express the desired learning. The design of differentiation learning designs with PBL content with 4C competencies is carried out in stages, namely literacy, critical thinking, collaboration, communication and creativity.